Development of a new 3D openFOAM (R) solver to model the cooling stage in profile extrusion - Fernandes, Célio Bruno Pinto (2016)
In this work a new solver is developed in OpenFOAM computational library, to model the cooling state in profile extrusion. The solver is able to calculate the temperature distribution in a two domain system, comprising the profile and calibrator, considering the temperature discontinuity at the interface. The derivation of the model is based on the local instantaneous energy conservation equation, in conjunction with the conditional volume averaging technique, which yields a single governing equation valid in both domains. Aiming the solution of automatic optimization/parameterization problems, the developed solver was coupled with the DAKOTA toolkit. The application of the novel calculation system is illustrated in a study of a complex geometry extruded profile cooling stage.